EFFICACY OF MESOTHERAPY WITH VITAMIN C IN PATIENTS OF MELASMA WITH FITZPATRICK SKIN TYPE IV & V - Dr Ayesha Rehman; Dr Ammara Azeem; Dr Mehwish; Dr Uzma Ahsan; Dr Sarah Khan (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Melasma is a skin disorder that is managed through various topical applications. But still dermatologists are in search for a better management plan. OBJECTIVE: To determine the outcome of mesotherapy with topical vitamin C in patients with melasma in Fitzpatrick skin type IV & V. Study Design: Quasi Experimental Study. Duration of Study: 02 April, 2022 to 02 October, 2022. Data Collection Procedure: Data was collected from patients presenting in OPD of Dermatology Department, Sharif medical city hospital, Lahore fulfilling the selection criteria. After approval from the ethical committee of hospital, an informed consent was obtained to include their data in the study. Melasma Area and Severity Index score(MASI) was calculated before first session and after end of third session by using Wood’s light. Microneedling was carried out in vertical, horizontal and both diagonal directions for about ten passes in each direction or till pinpoint bleeding occurs. Pure vitamin C of healer’s pharma was applied over all affected area. At the end of the study, photographs were recorded again to compare with baseline photographs, and outcome calculated on a pre-designed proforma. Data entry and analysis was done by using SPSS 23. Results: Mean age was 32.50±4.79 years. Majority of the cases were female 84(79.2%). Paired sample T test revealed that mean difference of the pre and post treatment MASI score was 3.83±1.86 with a significant difference. Conclusion: Mesotherapy with topical vitamin C is effective method in terms of the reduction of the mean MASI score.